Association between insertion/deletion polymorphism in angiotensin-converting enzyme gene and acute lung injury/acute respiratory distress syndrome: a meta-analysis - Matsuda Akihisa; Kishi Taro; Jacob Asha; Aziz Monowar; Wang Ping (BMC, 2012)
Abstract Background A previous meta-analysis reported a positive association between an insertion/deletion (I/D) polymorphism in the angiotensin-converting enzyme gene (ACE) and the risk of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS). Here, we updated this meta-analysis and additionally assessed the association of this polymorphism with ALI/ARDS mortality. Methods We searched electronic databases through October 2011 for the terms "angiotensin-converting enzyme gene", "acute lung injury", and "acute respiratory distress syndrome," and reviewed all studies that reported the relationship of the I/D polymorphism in ACE with ALI/ARDS in humans. Seven studies met the inclusion criteria, comprising 532 ALI/ARDS patients, 3032 healthy controls, and 1432 patients without ALI/ARDS. We used three genetic models: the allele, dominant, and recessive models. Results The ACE I/D polymorphism was not associated with susceptibility to ALI/ARDS for any genetic model. However, the ACE I/D polymorphism was associated with the mortality risk of ALI/ARDS in Asian subjects ( Pallele < 0.0001, Pdominant = 0.001, Precessive = 0.002). This finding remained significant after correction for multiple comparisons. Conclusions There is a possible association between the ACE I/D polymorphism genotype and the mortality risk of ALI/ARDS in Asians.